The Indonesia and Cambodia Cooperation in Accelerating Tourism Recovery Post Pandemic - Anwar, Miftahul; Candra, Rudi (Mediasi Journal of International Relations, 2023)
The COVID-19 pandemic has significant impact on the global tourism industry, including in Indonesia and Cambodia. To accelerate the recovery of the tourism industry, these two countries have cooperated in various aspects, such as improving health protocols, joint tourism promotion, and infrastructure development. This research aims to analyze the cooperation between Indonesia and Cambodia in accelerating post-pandemic tourism recovery. This research uses qualitative research methods and the concepts of international cooperation and nation branding. Data were collected through literature studies, as well as government and tourism practitioner websites from both countries. The results showed that cooperation between Indonesia and Cambodia in accelerating post-pandemic tourism recovery has been done through various initiatives. Related to improving the health protocols, both countries have exchanged information and experiences as well as cooperation in terms of joint tourism promotion. Both countries have promoted their tourism through their social media and promotional videos furthermore the two countries have also cooperated in infrastructure development, such as the construction of airports and ports. Indonesia and Cambodia can strengthen cooperation in tourism by increasing the exchange of information and experiences and promoting their tourist destinations. The concept of nation branding can be used to strengthen the tourism branding of both countries worldwide and increase tourist attraction. This research has practical implications for developing the tourism industry in Indonesia and Cambodia, as well as making theoretical contributions related to international cooperation in tourism and the concept of nation branding.